2010
DOI: 10.1002/jez.583
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of body volume constraint on female reproductive output

Abstract: The body volume constraint hypothesis is a widely accepted notion that explains proximate limitation of female reproductive output, but lacks empirical support. To examine how body volume determines reproductive output, we experimentally manipulated the body volume of female lacertid lizard (Takydromus septentrionalis), to examine whether a reduction in body volume caused a reduction in reproductive output. Clutch size and mass decreased with a reduction in body volume. Reproductive output (residual clutch mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The first of these predictions was largely verified by our data, both for offspring length and offspring mass (see Table 2), but the second predication was supported only for the thinner western ribbon snake. These outcomes support other studies that found that 'packaging' constraints are important in determining how the trade-off between litter size and offspring is modulated (Shine, 1992;Du et al, 2005;Du & Lu, 2010) and are consistent with experimental studies in lizards that showed when clutch size is experimentally reduced, offspring size increases (Sinervo, 1990;Olsson, Wapstra & Olofsson, 2002; Although the SVL of the largest reproductive female western ribbon snakes and checkered garter snakes were approximately the same, body masses of the checkered garter snakes were more than double the western ribbon snakes. Ji & Diong, 2006).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The first of these predictions was largely verified by our data, both for offspring length and offspring mass (see Table 2), but the second predication was supported only for the thinner western ribbon snake. These outcomes support other studies that found that 'packaging' constraints are important in determining how the trade-off between litter size and offspring is modulated (Shine, 1992;Du et al, 2005;Du & Lu, 2010) and are consistent with experimental studies in lizards that showed when clutch size is experimentally reduced, offspring size increases (Sinervo, 1990;Olsson, Wapstra & Olofsson, 2002; Although the SVL of the largest reproductive female western ribbon snakes and checkered garter snakes were approximately the same, body masses of the checkered garter snakes were more than double the western ribbon snakes. Ji & Diong, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…For species with a wide range of maternal body sizes, some of the apparent inconsistency between theoretical predictions and empirical data may relate to the allometric changes in body volume that occur with increase in the length of the female (Berrigan, ; Fischer, Zwaan & Brakefield, ; Feldman & Meiri, ). Scaling of body volume with length should allow longer females to have proportionally larger offspring because of relaxed constraints from increased body volume, but this is not usually the case (Bonnet et al ., ; Fischer et al ., ; Ji & Diong, ; Du & Lu, ). More often larger females will have the same size offspring as smaller females.…”
Section: Introductionmentioning
confidence: 99%
“…Morphology and reproduction can be closely linked in many organisms (Zúñiga‐Vega et al , 2007; Du & Lü, 2010). In many cases, body shape has evolved in response to selective pressures that directly affect reproductive traits (Forsman & Shine, 1995; Sinervo & De Nardo, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In either situation, a close link is expected between reproductive traits and body shape. Yet relatively few studies have attempted to disentangle cause and effect in these associations (Griffith, 1994; Du & Lü, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The relatively larger head benefits males in bouts of intrasexual combat (Huyghe et al, 2005;Lappin and Husak, 2005;Shine, 2005) and potentially amplifies food niche divergence between the sexes in species with a positive correlation between head size and prey size (Braña, 1996;Lin and Ji, 2000;Qiu et al, 2001;Zhang and Ji, 2004). In females, selection for increased reproductive output is correlated with an increase in abdomen size, causing an increase in the amount of abdominal volume available to hold the clutch (Shine, 1992;Olsson et al, 2002;Du et al, 2005;Du and Lü, 2010).…”
Section: Introductionmentioning
confidence: 99%